Nonlinear pricing with competition: The market for settling payments - Adam Copeland; Rod Garratt (Federal Reserve Bank of New York, 2015)
The multiple payments settlement systems available in the United States differ on several dimensions. The Fedwire Funds Service, a utility that operates a U.S. large-value paymentssettlement service, offers the fastest speed of settlement. Recognizing that payments differ in the urgency with which they need to be settled, Fedwire offers banks a decreasing block-price schedule. This approach allows Fedwire to price discriminate, charging high fees for urgent payments and low fees for less urgent ones. We analyze banks' demand for Fedwire Funds given this nonlinear scheme, taking into account competing settlement systems. We show that how banks respond to Fedwire's pricing depends crucially on the need to settle payments quickly. If the urgency for immediate settlement is great enough, banks will respond to marginal price; otherwise, they will respond to average price. We test whether banks respond to marginal or to average price. Our identification comes from exogenous variation in Fedwire's pricing, which results in differential changes in marginal and average price for comparable banks. We find that banks respond to average price.
Keywords: L11; L51; L97; E42; 330; nonlinear pricing; marginal versus average pricing